Effect of recombinant human nerve growth factor treatment on corneal nerve regeneration in patients with neurotrophic keratopathy - Balbuena-Pareja, Ana; Bogen, Chloe S.; Cox, Stephanie M.; Hamrah, Pedram (Frontiers in Neuroscience, 2023)
Introduction: Neurotrophic Keratopathy (NK) is a neurodegenerative corneal disease that results in diminished corneal sensation. Previous studies have found that Cenegermin 0.002%, a recombinant human nerve growth factor (rhNGF), improves corneal epithelial healing in stage 2 and 3 NK patients. However, rhNGF effect on corneal sensation and nerve regeneration has not been well established. Thus, this study aims to analyze the effect of rhNGF on corneal nerve regeneration using in vivo confocal microscopy (IVCM) and on corneal sensitivity in NK patients. Methods: This is a retrospective, longitudinal, case-control study that included patients with NK treated with rhNGF for at least 4 weeks, with pre- and post- treatment IVCM images available for analysis. Chart reviews were conducted documenting prior medical and surgical history, clinical signs and symptoms, and corneal sensation using Cochet-Bonnet esthesiometry. Corneal nerve parameters were assessed by IVCM. Sex- and age-matched reference controls were selected from a database of healthy subjects for comparison. Results: The study included 25 patients, with 22 (88%) stage 1, two (8%) stage 2, and 1 (4%) stage 3 NK, with a median age of 64 (range: 30 to 93 years). Total, main, and branch nerve densities [median (range) in mm/mm²] were lower in the NK group pre-treatment [2.3 (0.0 - 21.1); 1.7 (0.0 - 13.0); 0.5 (0.0 -10.2); respectively] vs. controls [22.3 (14.9 - 29.0); 10.1 (3.2 - 15.4); and 12.1 (6.2 - 18.4), (p< 0.0001 for all), respectively]. Post-treatment nerve densities increased compared to pre-treatment to 5.3 (0.0-19.4, p= 0.0083) for total, 3.5 (0.0-13.2, p= 0.0059) for main, and 2.0 (0.0-10.4, p= 0.0251) for branch nerves, but remained lower than controls (p< 0.0001 for all). Corneal sensation increased 2.3 ± 1.1 cm pre-treatment to 4.1 ± 1.4 cm post-treatment (p= 0.001). Median best corrected visual acuity significantly increased following rhNGF treatment from 0.4 (0.0 - 1.6) to 0.12 (-0.1 - 1.6) (p = 0.007). Conclusion: Patients with NK treated with at least 4 weeks of rhNGF showed a significant increase in corneal nerve densities after treatment. A significant increase in corneal sensation, as well as best corrected visual acuity was observed following treatment.